Cradle- to-gate life cycle assessment of poultry production system (2011)
The study assesses environmental impacts of hatchery production processes to point-of-lay and investigates effects of different scenarios on environmental load impacts in the Life Cycle Assessment (LCA) results. Functional unit of this LCA study is one poultry bird at point of lay and the activities associated within the system boundary. Results obtained showed that total contributions of the egg-point of lay system to global warming was 9.708kg of CO2 equivalents, 11.34 kg of CH4 equivalent, 0.2kg of N02, acidification was 2,713 x10-4kg of SO2 equivalents, 1.948 x 10-3 kg of NH3 equivalents, 2.167 x 10-3 kg of NOx equivalents and energy consumption was computed at 59.79KJ per bird, Hatchery process accounted for the highest consumption of energy of about 543.2J per bird, waste disposal accounted for about 6J per bird, while water pumping process consumed about 16J per bird, while feed production process-required about 46.5Jof energy, The LCA results showed that minimizing energy consumption in the hatchery process is the way forward in reducing environmental impact loads in a poultry system.Scenario analysis showed that using 100% public power supply will reduce the CO2, NOx and SO2 equivalents by 95.56%, 10.64% and 15.58%, while using 50-50% diesel public power supply will reduce CO2, NOx and 502 equivalents by 47.78%, 5.22% and 21.50% respectively.